2012
DOI: 10.1088/1367-2630/14/1/013061
|View full text |Cite
|
Sign up to set email alerts
|

Information-causality and extremal tripartite correlations

Abstract: We study the principle of information-causality (IC) in the presence of extremal no-signaling correlations on a tripartite scenario. We prove that all, except one, of the non-local correlations lead to violation of IC. The remaining non-quantum correlation is shown to satisfy any bipartite physical principle. Contents

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…For instance, the correlations provided in [7] violate GYNI and, consequently, also LO, but satisfy every bipartite principle. Also box number 4 in [29] is an example of a tripartite no-signaling box which cannot be ruled out by any bipartite principle [30], but which violates LO.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the correlations provided in [7] violate GYNI and, consequently, also LO, but satisfy every bipartite principle. Also box number 4 in [29] is an example of a tripartite no-signaling box which cannot be ruled out by any bipartite principle [30], but which violates LO.…”
Section: Resultsmentioning
confidence: 99%
“…The intrinsically multipartite character of the LO principle has allowed us to witness the supra-quantumness of box number 4 in [39], which cannot be achieved with any bipartite principle [40]. One example of an LO inequality in the (6, 2, 2) scenario which is violated by two copies of this box is given by…”
Section: Lo ∞ and Supra-quantum Tripartite Boxesmentioning
confidence: 99%
“…It has been shown that, some general physical principles can restrict the set of nosignalling correlations among distant observers to a significant degree. Information theoretic principles like information causality [1] and nontrivial communication complexity [2,3] are novel proposals to single out the quantum correlations, from rest of the no-signalling correlations, when two distant observers (or in some cases even when more than two observers [5]) are involved. However, by applying the known information principles to the bipartite case, it has not been possible to derive the full set of quantum correlations resulting from the Hilbert space structure of quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%